Accumulation and distribution of dry matter in cassava influenced by water stress. - Porto, Marcio Carvalho Marques; Cock, James H.; Cadena, Giovanna G. de; Parra, Germán E.; Hernández, Ana Del Pilar (Pesquisa Agropecuaria Brasileira, 2014)
Growth of cassava, cultivar M Cal 1684, was evaluated under water stress conditions established over a 100-day period of water exclusion, starting after three and six months from planting. The experiment was carried out in Santander de Quilichao, Colombia, on a lysimeter with 30m x 15m x 2,3m. Accumulation of total dry matter by the plants, measured at regular time intervals, was reduced by water stress, especially in the three month old plants. The same effects were evident on root dry weight. Water stress caused reductions in root dry weights and leaf areas of both groups of plants. In those stressed after three months of growth those reductions were due to lower rates of leaf formation and expansion, contrarily to plants stressed after six months, which reduced shoot weight and leaf area by an increase in leaf fall.